ANALYSIS OF USING ALTERNATIVE REFRIGERANTS FOR ENERGY SAVING IN DESIGN FRAMEWORK OF AIR-CONDITIONING SYSTEM - I Made Astina; Prihadi Setyo Darmanto; Warsito Warsito; Edwin Adryanto (Mesin, 2005)
Environmental issues enforce us to find environmental friendly alternative refrigerants. Increasing energy consumption as consequence of widespread usage of air-conditioning systems needs effort to find efficient systems. Use ability of alternative refrigerants and effect of modified vapor-compression cycles were investigated in this research. In figuring effects of their application on a real air-conditioning system, analysis of redesign of air-conditioning system was concerned to make clear the problem. The results confirm that a right selection of refrigerants to air-conditioning system can improve its performance. Energy saving and economical costs can be reduced significantly. Several groups of hydrocarbons (HC) and hydrofluorocarbons (HFC) have good thermodynamic performance and better than R-22 that will be phased out. By introducing these alternative refrigerants, carbon-dioxide (CO2) emissions can be reduced due to energy saving caused by increasing of the coefficient of performance (COP).